Business intelligence: a controladoria como vetor de sucesso com ênfase nos processos decisoriais - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This dissertation investigated the contribution of information technology tools, specifically Business Intelligence BI for the controllership area to exercise its function of supplying the decision-making process with the useful information it required. Thus, we sought to find out if the Business Intelligence, to be deployed in Infraero Manaus, would help in the process of providing information to management through the use of information technology. To achieve the objective of demonstrating the Comptroller model used in decision making and its importance in improving the managerial decision-making, from the implementation of Business Intelligence, this dissertation was tracked down the following specific objectives: to evaluate the Comptroller participation in all stages of business management; highlight the importance of Controlling the activities performed between the Accounting and Administration; and demonstrate through tangible results if there are consistent benefits after the implementation of BI model in the development of decisorial process in view of managers, controllers, of IT technicians and general users of information systems to the International Airport of Manaus Eduardo Gomes . The study was conducted through field research, especially in a case study, in which the matter could be discussed in detail. Therefore, interviews were applied, guided by a script built for this purpose and by a protocol previously developed for the study, as well as internal documents were analyzed, files and direct observation as a source of evidence. It lists the tools found so that the controller can play its role managerial functions; and explains the importance of the activities performed in accounting and administration from the Business Intelligence transform data into information ready to be used for controlling the management reporting to support decision making.
Keywords: Business Intelligence; Balanced Scorecard; Controladoria; Tomada de Decisão; Alinhamento Estratégico; Decision Making; CIÊNCIAS SOCIAIS APLICADAS: ADMINISTRAÇÃO: CIÊNCIAS CONTÁBEIS